267 INTESTINAL STEM CELL MARKERS AND ITS POTENTIAL USE IN THE CLINICOPATHOLOGICAL SETTING OF ESOPHAGEAL ADENOCARCINOMA. (17th September 2021) - Shibahara, Yukiko; Espin-Garcia, Osvaldo; Conner, James; Weiss, Jessica; Derouet, Mathieu; Allen, Jonathan; Wilson, Gavin; Allison, Frances; Kalimuthu, Sangeetha; Wong, Rebecca; Elimova, Elena; Yeung, Jonathan; et al.
Abstract: : Barrett's esophagus (BE) is the primary precursor lesion of esophageal adenocarcinoma (EAC), which not only resembles the intestinal mucosa morphologically but also expresses various intestinal stem cell (ISC) markers. We hypothesized that ISC markers, Lgr5 (also a cancer stem cell marker), Ascl2 (fate determinator of ISC), Bmi1 (quiescent counterpart of Lgr5) and Cdx2 (primary regulator of ISC gene expression) have clinicopathological significance and could potentially be a predictor for survival in EAC. Methods: Tissue microarray consisted of 64 EAC and 22 BE, and the expressions of Lgr5, Ascl2, Bmi1 and Cdx2 were analyzed using immunohistochemistry and scored independently by two pathologists. Clinicopathological factors (age, pathological grade and stage, affected lymph nodes, neoadjuvant therapy) were confounding factors, and univariable analysis using Fisher's exact tests as well as survival analysis using the Kaplan–Meier (KM) method and Cox proportional hazards regression (Cox PH) were performed to investigate its statistical significance. We performed a bioinformatic analysis of the TCGA dataset to validate the immunohistochemical findings. Results: Among EAC, 69%, 88%, 64% and 70% expressed high Ascl2, Lgr5, Bmi1 and Cdx2, respectively. High Ascl2 and low Lgr5 expression significantly correlated to a higher number of involved lymph nodes; high Bmi1 expression significantly correlated to the pathological stage. Cdx2 was not correlated to any markers. KM analysis showed a negative impact of high Ascl2 expression on overall survival (OS; p = 0.0276) as well as progression-free survival (PFS; p = 0.0466), but not Lgr5, Bmi1 nor Cdx2. Cox PH analysis revealed Ascl2 (p = 0.011), and Cdx2 (p = 0.015) expression are independent prognostic factors for EAC. Conclusion: Our results suggest that among the four ISC markers, Ascl2 and Cdx2 protein holds potential to be utilized as a prognostic biomarker. TCGA dataset revealed the association of ASCL2 mRNA expression with the number of positive lymph nodes but not overall survival, which implies further research is needed to explain the mechanism of Ascl2 overexpression in EAC carcinogenesis via ISC regulation.